1997
DOI: 10.1128/jcm.35.1.59-63.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification of capsular antigens in Serratia marcescens

Abstract: Previous studies with 31 strains of Serratia marcescens, including 28 reference O-serotype strains, have indicated that 19 of them have an acidic polysaccharide which copurifies with lipopolysaccharide during phenol-water extraction. Polysaccharide in crude extracts from 18 of the 19 strains was precipitated with Cetavlon (hexadecyltrimethyl ammonium bromide), and capsules were demonstrated around these 18 strains by Indian ink exclusion zones. Capsule-antibody binding by the Quellung reaction suggested that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…We analyzed the morphologies of wild-type, YODUd, and SPRAd spores using phase-contrast microscopy and a negative staining procedure. When the spores were negatively-stained with Indian ink [31] , which is a stain commonly used to reveal polysaccharide capsules, a clear halo was visible around the wild-type spores, but not around the YODUd and SPRAd spores ( Figure 6A , top panels). The appearance of a halo is consistent with the presence of polysaccharides around the wild-type spore.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the morphologies of wild-type, YODUd, and SPRAd spores using phase-contrast microscopy and a negative staining procedure. When the spores were negatively-stained with Indian ink [31] , which is a stain commonly used to reveal polysaccharide capsules, a clear halo was visible around the wild-type spores, but not around the YODUd and SPRAd spores ( Figure 6A , top panels). The appearance of a halo is consistent with the presence of polysaccharides around the wild-type spore.…”
Section: Resultsmentioning
confidence: 99%
“…B. subtilis spores were negatively stained with Indian ink, as previously described [31] with a slight modification. The purified spores were resuspended in DDW, and 2 µl of the suspension was mixed with an equivalent volume of Indian ink (Daiso Sogyo, Japan) on a slide glass.…”
Section: Methodsmentioning
confidence: 99%
“…Phage-resistant acapsular variants of 11 of the 29 reference strains had been produced for a previous study (Aucken et al , 1997). These variants were used here for adsorption of O antibodies from sera to the encapsulated reference strains to produce K-specific typing reagents.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical analysis of polymers present in ‘ LPS ’ extracts from the reference strains has shown that the polysaccharide repeating units can be divided into neutral and acidic structures and that many of the reference strains possess both (Wilkinson, 1990). It has been suggested that the LPS 0 antigens correlate with the neutral polysaccharides (Gaston et al, 1988 ; Gaston & Pitt, 1989a) while the acidic polysaccharides have now been shown to correspond to capsular antigens (Aucken et al, 1997). The current study was undertaken to rationalize the existing 0 typing scheme and to propose a complementary capsular K typing scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical tests including those of growth temperature, lactic acid isomer, and carbohydrate fermentation were performed. The Indian ink method was used to visualize bacterial capsules (Aucken et al, 1996). Plasmid DNA analysis of the strains was performed according to the method of Anderson and McKay (1983).…”
Section: Characteristics Of the Mutant Strainmentioning
confidence: 99%